2014
DOI: 10.1017/s1460396914000193
|View full text |Cite
|
Sign up to set email alerts
|

Image guidance procedures in radiotherapy for prostate cancer and the influence of body mass index

Abstract: Purpose: To investigate possible optimisation of the image guidance procedure for the prostate cancer patients with respect to imaging frequency and patient body mass index (BMI).Methods: The 6,085 setup correction shifts and BMI for 216 prostate cancer patients treated on tomotherapy units in two centres were analysed. Margins needed to account for inter-fraction target motion with daily only automatic correction and with automatic and manual corrections during one, three or five first fractions as a referenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
3
0
3
Order By: Relevance
“…For example, one study demonstrated benefits to daily imaging for obese and overweight patients (BMI .25), whereas the patients with normal BMI could be treated with imaging guidance restricted to the first few initial treatment fractions with calculated patientspecific set-up corrections applied thereafter. 79 Schulze et al 80 evaluated the possible effect of online daily replanning and estimated better organ-at-risk sparing: the rectum and bladder doses were lower by 11% and 14%, respectively. With CBCT pretreatment imaging, matching based on bony anatomy, soft tissue and online reoptimization was evaluated using the 10-and 5-mm PTV margins.…”
Section: Patient-specific Margins and Adapted Radiotherapymentioning
confidence: 99%
“…For example, one study demonstrated benefits to daily imaging for obese and overweight patients (BMI .25), whereas the patients with normal BMI could be treated with imaging guidance restricted to the first few initial treatment fractions with calculated patientspecific set-up corrections applied thereafter. 79 Schulze et al 80 evaluated the possible effect of online daily replanning and estimated better organ-at-risk sparing: the rectum and bladder doses were lower by 11% and 14%, respectively. With CBCT pretreatment imaging, matching based on bony anatomy, soft tissue and online reoptimization was evaluated using the 10-and 5-mm PTV margins.…”
Section: Patient-specific Margins and Adapted Radiotherapymentioning
confidence: 99%
“…Podstawowym celem weryfikacji obrazowej jest ocena zgodności pomiędzy aktualną anatomią pacjenta (przed podaniem dawki frakcyjnej) z anatomią pacjenta zobrazowaną przed rozpoczęciem kursu radioterapii, dla której został utworzony plan leczenia, oraz redukcja wykrytych w trakcie powyższej oceny rozbieżności poprzez korekcję ułożenia pacjenta [5][6][7][8][9].…”
Section: Wstępunclassified
“…Dlatego też korekcja ułożenia pacjenta poddanego radioterapii raka stercza na podstawie struktur kostnych obarczona jest błędem [22]. Błąd ten jest zredukowany w przypadku korekcji ułożenia przeprowadzonego na podstawie dopasowania tkanek miękkich (CBCT) [7]. Celem niniejszej pracy było określenie błędu, jakim obarczona jest metoda 2D-kV w porównaniu z metodą CBCT.…”
Section: Materiał I Metodaunclassified
See 1 more Smart Citation
“…have shown that daily IG is needed for obese patients while the patients with body mass index <30 will benefit from IG procedures performed only during a few first treatment fractions. [ 4 ] A limited number of pretreatment IG sessions presents as an interesting compromise that allows for savings on labor, time, and imaging dose while taking into account specific information about target motion with the construction of personalized margins for the subsequent fractions without IG. [ 5 ]…”
mentioning
confidence: 99%